Public health significance of the white-tailed deer (Odocoileus virginianus) and its role in the eco-epidemiology of tick- and mosquito-borne diseases in North America - Ilia Rochlin; Joan Kenney; Eliza Little; Goudarz Molaei (Parasites & Vectors)
Abstract White-tailed deer (Odocoileus virginianus) are a ubiquitous species in North America. Their high reproductive potential leads to rapid population growth, and they exhibit a wide range of biological adaptations that influence their interactions with vectors and pathogens. This review aims to characterize the intricate interplay between white-tailed deer and the transmission cycles of various tick- and mosquito-borne pathogens across their range in the eastern United States and southeastern Canada. The first part offers insights into the biological characteristics of white-tailed deer, their population dynamics, and the consequential impacts on both the environment and public health. This contextual backdrop sets the stage for the two subsequent sections, which delve into specific examples of pathogen transmission involving white-tailed deer categorized by tick and mosquito vectors into tick-borne and mosquito-borne diseases. This classification is essential, as ticks and mosquitoes serve as pivotal elements in the eco-epidemiology of vector-borne diseases, intricately linking hosts, the environment, and pathogens. Through elucidating these associations, this paper highlights the crucial role of white-tailed deer in the transmission dynamics of tick- and mosquito-borne diseases. Understanding the interactions between white-tailed deer, vectors, and pathogens is essential for effective disease management and public health interventions. Graphical Abstract